ANALYSIS OF FLAVONOID COMPOUNDS OF GANDARIA FRUIT (Bouea macrophylla GRIFF) AT VARIOUS Elevations IN AMBON ISLAND - Papilaya, Pamella Mercy; Karuwal, Ritha; Patadungan, Ayu Kristin (BIOPENDIX: Jurnal Biologi, Pendidikan dan Terapan, 2024)
Introduction: Gandaria (Bouea macrophylla Griff) is a tropical fruit plant which in the Maluku region is only found in several areas, namely Ambon Island as the largest production center. Gandaria contains secondary metabolites, one of which is flavonoids, which are generally found in various plants and are very potential to be researched and developed by Indonesian researchers because they have many good benefits for living things. Methods: This study used qualitative and quantitative research methods to test the color of the gandaria fruit samples to identify the presence of flavonoid compounds and then to find out how much flavonoids were in the gandaria fruit research samples taken from various altitudes on Ambon island. Results: The results of this study indicate that the Suli area as the area with the lowest altitude where the sample was taken contains the highest levels of flavonoids with an average of 21.498 mgQE/g, then the area of medium altitude where the sample is taken, namely Kusu-kusu has a flavonoid content with an average of 9.692 mgQE/g then in the area with the highest altitude level in sampling, namely Soya with the lowest flavonoid content with an average flavonoid content of 9.084 mgQE/g.